208k views
2 votes
Which choice is equivalent to the expression below?

Which choice is equivalent to the expression below?-example-1
User David Gee
by
4.4k points

2 Answers

3 votes

Answer:

B. 7√10.

Explanation:

√40 = √4√10 = 2√10

√90 = √9√10 = 3√10

So √40 + 2√10 + √90

= 2√10 + 2√10 + 3√10

= 7 √10.

User Mohabouje
by
4.5k points
4 votes

ANSWER

B. 7√10

EXPLANATION

The given radical expression is:


√(40) + 2 √(10) + √(90)

We need to remove the perfect square from the first and third term.


√(4 * 10) + 2 √(10) + √(9 * 10)

We now share the radical sign to get;


√(4) * √(10) + 2 √(10) + √(9) * √(10)

Simplify to get;


2√(10) + 2 √(10) + 3 √(10)

This simplifies to


7 √(10)

User Stitty
by
5.6k points